Omega‐3 polyunsaturated fatty acid supplementation attenuates blood pressure increase at onset of isometric handgrip exercise in healthy young and older humans. Issue 14 (20th July 2016) - Clark, Christine M.; Monahan, Kevin D.; Drew, Rachel C.
Abstract: Aging is associated with alterations of autonomic nerve activity, and dietary intake of omega‐3 polyunsaturated fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) found in fish oil (FO), can modulate autonomic nerve activity. However, the effect of omega‐3 polyunsaturated fatty acid consumption on age‐related cardiovascular responses at the onset of isometric handgrip exercise, a time of rapid autonomic adjustments, is unknown. Accordingly, 14 young (25 ± 1 years; mean ± SE) and 15 older (64 ± 2 years) healthy subjects ingested 4 g FO daily for 12 weeks. On pre‐ and postintervention visits, participants performed 15‐sec bouts of isometric handgrip at 10%, 30%, 50%, and 70% maximal voluntary contraction (MVC) while beat‐to‐beat systolic, diastolic, and mean arterial blood pressure (SBP, DBP, MAP; Finometer) and heart rate (HR; electrocardiogram) were recorded. All baseline cardiovascular variables were similar between groups and visits, except DBP was higher in older subjects ( P < 0.05). FO increased erythrocyte EPA and DHA content in both groups ( P < 0.05). FO attenuated MAP and DBP increases in response to handgrip in both age groups (change from baseline during 70% MVC handgrip pre‐ and post‐FO: young MAPΔ 14 ± 2 mmHg versus 10 ± 2 mmHg, older MAPΔ 14 ± 3 mmHg versus 11 ± 2 mmHg; young DBPΔ 12 ± 1 mmHg versus 7 ± 2 mmHg, older DBPΔ 12 ± 1 mmHg versus 7 ± 1 mmHg; P < 0.05). FO augmented the PP (SBP‐DBP) increase with 70% MVC handgrip in both groups ( P < 0.05), but did not alter SBP or HR increases with handgrip. These findings suggest that FO supplementation attenuates MAP and DBP increases at the onset of isometric handgrip exercise in healthy young and older humans. Abstract : Results from this study show that daily fish oil supplementation for 12 weeks attenuated increases in mean arterial and diastolic blood pressure at the onset of isometric handgrip exercise in healthy young and older subjects. This novel finding suggests that dietary intake of omega‐3 polyunsaturated fatty acids reduces the cardiovascular response to acute physiological stress, and this modulatory effect occurs irrespective of age.